THE EFFECTIVENESS OF TEACHING PHYSICS THROUGH PEDAGOGICAL INNOVATIONS - Mammadli Aytan Alik (Modern American Journals, 2025)
In the modern era, the development of the education system is closely linked to the implementation of pedagogical innovations. The use of innovative methods and technologies in teaching physics increases students’ interest in the subject and helps develop their creativity and research skills. The article analyzes the main types of pedagogical innovations, their application possibilities in physics lessons, and the outcomes. The presented results play a key role in improving the quality of the teaching process.
Keywords: Pedagogical innovation, physics teaching, effectiveness, technology, creativity.